2004
DOI: 10.1002/jemt.20042
|View full text |Cite
|
Sign up to set email alerts
|

An EBSP study of isothermally‐annealed cold‐rolled nickel

Abstract: Scanning electron microscopy and electron backscattered patterns, EBSP, have been employed to reveal both the grain structure and texture of 90% cold-rolled polycrystalline nickel after 1-hour anneals at a variety of temperatures. After annealing at either 400 degrees or 500 degrees C, small, cube-oriented, equi-axed grains were produced via primary recrystallization. At 600 degrees C, large [124]<211> oriented grains accounted for an increasing proportion of the microstructure, until at 1000 degrees C only la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…A previous study [4,5] on the directional recrystallization of 90 pct cold-rolled, 99.5 wt pct purity, polycrystalline nickel suggested that a strong primary recrystallization texture-for nickel, the cube texture-is necessary for growing single crystals or columnar grains upon directional annealing at secondary recrystallization temperatures. The growth mechanism of the columnar grains or single crystals was also discussed.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study [4,5] on the directional recrystallization of 90 pct cold-rolled, 99.5 wt pct purity, polycrystalline nickel suggested that a strong primary recrystallization texture-for nickel, the cube texture-is necessary for growing single crystals or columnar grains upon directional annealing at secondary recrystallization temperatures. The growth mechanism of the columnar grains or single crystals was also discussed.…”
Section: Introductionmentioning
confidence: 99%
“…CG Ni foils with commercial purity were purchased from Alfa Aesar. Since the as-received CG Ni was cold rolled, recrystallization annealing was preformed at 450°C for 3 h [27]. In situ neutron diffraction with a time-of-flight method was conducted using SMARTS hydraulic load-frame at Los Alamos Neutron Science Center.…”
Section: Methodsmentioning
confidence: 99%
“…Grainboundary texture is a subject of study for a number of researchers. In the view of the present work, few important aspects can be noted from the results of Baker and Li [14]. In this paper, the authors have summarized results obtained by different researchers.…”
Section: Effect Of Cold Rolling and Grain Boundary Crystallographymentioning
confidence: 86%
“…The /111S or /10 0S preferential rotation direction can be controlled by rolling procedure. Makita et al [16] and other workers [14] have emphasized the role of CSL that CSL boundaries around large grains have higher mobility than other boundaries. They have also noted {11 0} /11 2S orientation relationship and explained it as related to twin orientation.…”
Section: Effect Of Cold Rolling and Grain Boundary Crystallographymentioning
confidence: 98%
See 1 more Smart Citation